Polypyrenes as High‐Performance Cathode Materials for Aluminum Batteries. Issue 15 (7th March 2018) - Walter, Marc; Kravchyk, Kostiantyn V.; Böfer, Cornelia; Widmer, Roland; Kovalenko, Maksym V.
Abstract: The pressing need for low‐cost and large‐scale stationary storage of electricity has led to a new wave of research on novel batteries made entirely of components that have high natural abundances and are easy to manufacture. One example of such an anode–electrolyte–cathode architecture comprises metallic aluminum, AlCl3 :[EMIm]Cl (1‐ethyl‐3‐methylimidazolium chloride) ionic liquid and graphite. Various forms of synthetic and natural graphite cathodes have been tested in recent years in this context. Here, a new type of compelling cathode based on inexpensive pyrene polymers is demonstrated. During charging, the condensed aromatic rings of these polymers are oxidized, which is accompanied by the uptake of aluminum tetrachloride anions (AlCl4 − ) from the chloroaluminate ionic liquid. Discharge is the fast inverse process of reduction and the release of AlCl4 − . The electrochemical properties of the polypyrenes can be fine‐tuned by the appropriate chemical derivatization. This process is showcased here by poly(nitropyrene‐ co ‐pyrene), which has a storage capacity of 100 mAh g −1, higher than the neat polypyrene (70 mAh g −1 ) or crystalline pyrene (20 mAh g −1 ), at a high discharge voltage (≈1.7 V), energy efficiency (≈86%), and cyclic stability (at least 1000 cycles). Abstract : Pyrene‐based polymers are demonstrated as high‐performance cathode materials for aluminum batteries delivering capacities of up to 100 mAh g −1 at an average voltage of 1.7 V for at least 1000 cycles.